2013
DOI: 10.1136/bmjquality.u201878.w997
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in Respiratory Medicine: Designing and implementing a bronchoscopy checklist at Southend University Hospital

Abstract: There is currently no standardised procedure checklist for bronchoscopies in the United Kingdom. Furthermore, very few hospitals appear to routinely use any form of checklist for these procedures. Conversely, the World Health Organisation surgical checklist has become standard practice in most hospitals, our own included, for all surgical procedures. Based on our own needs, we decided to create a bronchoscopy checklist which could be used at our hospital with the primary emphasis on ensuring patient safety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A key takeaway from this study is the incorporation of such guidelines or protocol, but with a goal of reducing waiting times and improving satisfaction among patients and proceduralists within the same day of the operation. By establishing our own bronchoscopy suite, we were able to initiate development of protocols for our own operation schedules and systems management [3]. Prior to establishing our own bronchoscopy suite, some of the conflicts our program experienced included ongoing conflict with gastroenterology service regarding scheduling different operations in one room, identifying whether our cases are being posted in a timely manner, and endoscopy technicians not experienced in bronchoscopies affecting workflow in the room due to inconsistencies in completing appropriate preoperative tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key takeaway from this study is the incorporation of such guidelines or protocol, but with a goal of reducing waiting times and improving satisfaction among patients and proceduralists within the same day of the operation. By establishing our own bronchoscopy suite, we were able to initiate development of protocols for our own operation schedules and systems management [3]. Prior to establishing our own bronchoscopy suite, some of the conflicts our program experienced included ongoing conflict with gastroenterology service regarding scheduling different operations in one room, identifying whether our cases are being posted in a timely manner, and endoscopy technicians not experienced in bronchoscopies affecting workflow in the room due to inconsistencies in completing appropriate preoperative tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search also recognized various quality improvement studies aimed at improving efficiency in the bronchoscopy procedure suites. Various projects have utilized similar measures from surgical specialties to determine if similar yields could be obtained, such as a surgical checklist prior to each procedure [3]. For our institution, we designed a quality improvement project with a goal of improving patient turnover and decreasing transit time between scheduled bronchoscopy cases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Similarly Pronovost et al [ 10 ] have shown that central venous catheter associated sepsis can be abolished by adhering to best practice through use of a customised checklist. In view of this evidence, it is plausible that safety checklists have a place in interventional procedures such as GI endoscopy [ 11 ], bronchoscopy [ 12 ], and interventional radiology. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%